Women's decision process when actively choosing to 'go flat' after breast cancer: a constructivist grounded theory study - Anna Paganini; Linda Myrin Westesson; Emma Hansson; Susanne Ahlstedt Karlsson (BMC, 2024)
Abstract Objective This study aims to describe a conceptual model that could illuminate the decision process women go through when choosing to go flat on one or both sides due to breast cancer. Methods A qualitative design, with constructivist grounded theory was used. Eighteen women were individually interviewed, digitally or by telephone, until saturation was reached. Data were analysed using a constant comparative iterative method in accordance with grounded theory. By examining the text data to identify the decision process for going flat and rejecting reconstructive surgery open coding was obtained. As the study proceeded patterns were explored and categories developed into a core category. Results The overall decision process for women choosing to go flat on one or both sides emerged in three phases: Phase 1, where the women are forced to "Face the cancer", Phase 2 comprising "Reflections on health and motivation" and Phase 3, described as "Hobson's choice". The fundament of the decision process was found in the core category "Establishing and safeguarding the chosen self". Conclusions The decision process involved in actively going flat and rejecting reconstructive surgery is founded in the individual woman's motivations, such as view of femininity and apprehensions about the offered reconstructive surgery.